Pengaruh Beban Kerja Dan Kompetensi Terhadap Prestasi Kerja Pegawai Dinas Perumahan Rakyat Kawasan Permukiman Dan Lingkungan Hidup Ciamis - Ditha Yulia Azzahra; Arga Sutrisna; Kusuma Agdhi Rahwana (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research was conducted with the aim to determine the simultaneous and partial effect of Workload and Competence on the Work Performance of the Public Housing Office of the Residential and Environmental Areas of Ciamis Regency. The research method used is descriptive method with a quantitative approach. The population in this study were 165 employees and a sample of 55 employees.The sampling technique used is Non-Probability Sampling (Departmental Sampling). Test data in this study include validity tests, reliability tests, and classical assumption tests. The data analysis tool used is multiple regression, correlation coefficient, and determination coefficient. Based on the results of the study it can be seen that Workload and Competence simultaneously have a significant effect on Office Work Performance Public Housing Residential and Environmental Areas of Ciamis Regency. Workload partially has a significant effect on the Work Performance of the Public Housing Office for Residential Areas and the Environment in Ciamis Regency. Competence partially has a significant effect on the Work Performance of the Public Housing Office for Settlement Areas and the Environment in Ciamis Regency.